2021
DOI: 10.1155/2021/5533980
|View full text |Cite
|
Sign up to set email alerts
|

A Solution to the Time‐Dependent Stress Distribution in Suborbicular Backfilled Stope Interaction with Creeping Rock

Abstract: The creep behavior of deep weak rock masses is important due to an underground opening. Appreciating the nature and source of these deformations requires the knowledge of rock mass and ground support interaction. The theoretical solution of the backfill’s internal stresses needs to consider the time-dependent effect. In the present study, the coupling interaction between the creep behavior of the nearby rock material and the internal stresses in the backfilled stope is considered and the interaction characteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…At the moment, FA is mainly used as an additive for cement and the preparation of cementitious materials, while DG is mainly used to prepare gypsum-based new building materials [12,13]. Numerous scholars and engineers have conducted the feasibility of the above two types of solid waste utilization [14,15]. It was found that the risk assessment codes in FA posed no or low risk [16], while the heavy metals in DG showed a medium risk to the ecosystem [17].…”
Section: Introductionmentioning
confidence: 99%
“…At the moment, FA is mainly used as an additive for cement and the preparation of cementitious materials, while DG is mainly used to prepare gypsum-based new building materials [12,13]. Numerous scholars and engineers have conducted the feasibility of the above two types of solid waste utilization [14,15]. It was found that the risk assessment codes in FA posed no or low risk [16], while the heavy metals in DG showed a medium risk to the ecosystem [17].…”
Section: Introductionmentioning
confidence: 99%
“…e drop in e value causes the water drainage and a sharp rise in the fill's density. is causes the continued hydration process to generate bigger quantities of hydration product that fills the spaces between particles, thus significantly reducing the void ratio [52]. is is not the case for CPB-D1 and CPB-D2 samples, although the void ratios were noticeably reduced in all samples.…”
Section: Assessment Of Voidmentioning
confidence: 89%
“…24 Yan et al's study research explains the coupling effect of creep behavior and internal pressure in backfill stope and calculates the theoretical solution considering the time effect to verify the correctness. 25 To address limitations in numerical simulation software models, many scholars frequently adopt combined element models to simulate measured stress-strain-time curves. They introduce damage mechanics and fracture mechanics to reflect the constitutive model of damage accumulation and crack propagation during the aging deformation of rock mass.…”
Section: Introductionmentioning
confidence: 99%
“…Yan et al's study research explains the coupling effect of creep behavior and internal pressure in backfill stope and calculates the theoretical solution considering the time effect to verify the correctness 25 …”
Section: Introductionmentioning
confidence: 99%